The Contribution of Ethical Leadership in Promoting the Educational and Learning Process in Greece - Geropoulos, Panagiotis; Tsioumis, Kostis (Journal of Education and Training, 2022)
The present work aims to approach the characteristics of ethical leadership and to detect the practices applied by the principals of secondary schools to support socially vulnerable groups. In this context, school leaders express views on the structure and "nature" of leadership, and in particular on ethical leadership. At the same time, emphasis is placed on capturing the implementation of actions for the educational support of the specific groups of the population as well as on the existing structure of the Greek educational system that operates restrictively for the undertaking of initiatives by them. It investigates whether the positive influences of ethical administration are not limited to the level of school units. In addition, the work seeks to identify the current problems that principals face in the performance of their duties. The analysis of the data from the 43 semi-structured interviews reveals important facts about the importance of ethical educational leadership and the benefits it can offer to the entire student population and to the operation of the school. In particular, the application of ethical leadership creates the right conditions to improve the learning performance of students, contributes positively to the socialization of vulnerable groups and finally creates a positive educational climate.